The Use Of Assistive Technology And Its Impact On Students With Autism Spectrum Disorder In The Inclusive Classroom From Teachers’ Perspectives - Alsalahat, Feras Abdel Rahman Salameh (2024)
The UAE is actively promoting the use of modern technologies, especially for individuals facing special challenges. This study explores the role of knowledge, attitudes, and challenges in shaping teachers' opinions about the impact of assistive technologies on the academic achievement, language, and behavior of students with autism spectrum disorder (ASD) in inclusive classrooms. The study aimed to determine the categories of students with autism spectrum disorder that benefit most from high-tech assistive technologies, the challenges facing school teachers when they use assistive technologies within the inclusive classroom, and to explore teachers’ knowledge about autism spectrum disorder and their attitudes toward integrating them into inclusive classrooms. The study methodology was exploratory and descriptive, and 275 teachers and 11 educational coordinators participated in the study. Quantitative data through questionnaires and qualitative data through interviews were used. The results of the study showed that first-level students on the autism spectrum benefit most from high-tech assistive technology. The most important challenges facing teachers were presented, and solutions were proposed. The study also explored teachers' knowledge about autism, their attitudes toward its inclusion, and the impact of these variables on their opinions about the impact of high-tech assistive technologies on students with autism spectrum disorder.